Development of Education and Training Models in Improving the Professionalism of Economic Teachers - Budiwati, Neti (International Journal Pedagogy of Social Studies, 2019)
The aim to develop models of education and training that are effective in improving teacher competencies. The research method uses non-experimental explanatory and R D method. The research sample is a high school economic teacher in the Greater Bandung area. Data collection using a questionnaire. Based on the education and training model that was once followed by economic teachers, the results of the research showed that teachers of professional education and training are very helpful in improving teacher professionalism, the form of online learning is very difficult for teachers, especially those in remote areas. Therefore teachers strongly agree to use face-to-face patterns and material support in improving teacher professionalism. Besides that the teacher strongly agrees that the Teacher Professional Education and Training and the teacher learning program with online mentoring can improve literacy and teachers who support professionalism. Teachers state patterns of teacher certification through Professional Education and Training Teachers should focus on professional competence. This study can determine the alternative development of the Teacher's Professional Education and Training model in positions and models, namely Teacher Professional Education and Training using blended learning and Teacher Education and Training Model Based on needs.